AFFIXES ANALYSIS IN A “HANSEL AND GRETEL” STORY TO ENGLISH YOUNG LEARNERS: A MORPHOLOGY PERSPECTIVE - Paramita Kusumawardhani (Wanastra: Jurnal Bahasa dan Sastra, 2020)
The aims of this research are to know about kinds of affix and how they are used in a story. Affixation is a part of morphology and it is a morphological process. Morphology is the study of the internal structure of words, so it deals with the structure of words. It also relates with morpheme. There are two kinds of morphemes, they are: free morpheme and bound morpheme and bound morphemes are related to derivational and inflectional. Derivational morphology is related to affixes. Affixes can be distinguished by two primary types, they are: prefixes and suffixes. Prefixes are attached at the beginning of a lexical item or base morpheme; meanwhile, suffixes are attached at the end of a lexical item or base morpheme. Affixes are related to affixation. Affixation is adding established prefix and suffix to the existing base. There are two ways of affixes; (1) according to the positions and (2) according to the functions. According to the positions, there 3 types of affixes, they are prefix, infix and suffix. According to the functions, there 2 types of affixes, they are derivational affixes and inflectional affixes. Derivational affixes cause the semantic change, such as bake – baker, happy – unhappy, like – dislike; and category change, such as run (verb) – runner (noun), dangerous (adjective) – dangerously (adverb), writing (noun) – write (verb). Affixations are common used in a story. They are used as the words change a form or meaning depends on the sentence. The participants of this research are the students at one of English Courses in Gading Serpong, Tangerang. Class Action Research (CAR) was used as the method to do the research. The results of this research are: there are 2 prefixes found in the story, they are re- and step-, meanwhile there 5 suffixes found in the story, they are -er, -ed, -s, -ly and -ing.